Determination of indicators of female athletes' speed movement engaging in rowing - Rovny, A.; Shaposhnikova, I.; Korsun, S. (Slobozhanskyi herald of science and sport, 2020)
Purpose: to determine the assessment criteria of speed abilities as indicators of the basis for the performance of female athletes` motor actions. Materials and methods: the analysis of speed abilities of 13-18 years female athletes engaging in rowing during the modeled training and competitive activity is carried out according to the developed method, namely: rate, time and speed of single movement, movement frequency, sensor motor response to sound and light stimulus. Results: the obtained results characterize the individual peculiarities of psychophysiological features of female athletes` organism in terms of modeling of sports activities, which makes it possible to make adjustments during the management of the training process. Conclusions: based on the analysis of research results the assessment criteria of physical quality of speed and its components were developed: rate, time of single movement speed, movement frequency to determine the prospects of female athletes as one of the components of the selection methodology. The proposed technique is recommended to be used at different stages of improving sports training.